Death at the White Hart - Chibnall, Chris (Pamela Dorman Books/Viking, 2025)
"From the internationally award-winning creator of Broadchurch comes a brilliant new detective story following one man's death and the secrets that unravel in a coastal English village Nothing keeps a village together like secrets. The villagers of Fleetcombe like to think of it as one of the most picturesque spots on England's coast. But now, it's a disturbingly macabre crime scene. A man is found dead, tied to a chair in the middle of the road, a stag's antlers on his head. The gruesome scene stuns the town, especially when the victim is identified: Jim Tiernan, who ran the White Hart pub. Tierney's pub is at the center of village life and he knew everyone's secrets. Detective Nicola Bridge grew up in Fleetcombe and has now returned, for the good of her family, from a life away in Liverpool. DC Harry Ward is ten years younger and, despite his newcomer status, determined to earn Nicola's trust. Because they don't have long to crack the storybook façade and find out just what the people of Fleetcombe have to hide. And now, in the place she thought she knew so well, Detective Nicola Bridge is asking questions. Is she ready for what she's about to find?"--